A High‐Voltage Zn–Organic Battery Using a Nonflammable Organic Electrolyte. Issue 38 (11th August 2021) - Qiu, Xuan; Wang, Nan; Dong, Xiaoli; Xu, Jie; Zhou, Kang; Li, Wei; Wang, Yonggang
Abstract: Owing to undesired Zn corrosion and the formation of Zn dendrites in aqueous electrolytes, most of the examples of aqueous Zn batteries with reported excellent performance are achieved with low Zn‐utilization (<0.6 %) in the anode and low mass‐loading (<3 mg cm −2 ) in the cathode. Herein, we propose a new organic electrolyte for Zn batteries, which contains a zinc trifluoromethanesulfonate (Zn‐TFMS) salt and a mixed solvent consisting of propylene carbonate (PC) and triethyl phosphate (TEP). We demonstrate that this electrolyte with an optimized PC/TEP ratio not only exhibits high ionic conductivity and a wide stable potential window, but also facilitates dendrite‐free Zn plating/stripping. In particular, the TEP solvent makes the electrolyte nonflammable. Finally, a 2 V Zn//polytriphenylamine composite (PTPAn) battery is fabricated with the optimized electrolyte; it shows a high rate and a long lifetime (2400 cycles) even with a high mass‐loading (16 mg cm −2 ) of PTPAn in the cathode and with a high Zn‐utilization (3.5 %). Abstract : A high‐voltage Zn–organic battery using a nonflammable organic electrolyte shows a long lifetime (2400 cycles) even with a high mass‐loading of 16 mg cm −2 in the cathode and high Zn‐utilization (3.5 %) in the anode. TFMS=trifluoromethanesulfonate, TEP=triethyl phosphate, PC=propylene carbonate.